The Operationalization of Ernesto Laclau’s Theory of Populism: Case of the Political Party “The Way of Courage” - Jonutis, Karolis (Sociologija. Mintis ir veiksmas, 2018)
This article aims to explain the rise of the Lithuanian political party “The Way of Courage” using Ernesto Laclau’s discourse theory of populism, in which populism is understood as a logic of collective identity formation. The advantages of this theoretical approach are revealed by comparing it with other tendencies of conceptualizing populism. In addition, this article is an attempt to solve the main disadvantage of E. Laclau’s theory – its high level of abstractness, understood as an obstacle for operationalization. Therefore, various possibilities of combining E. Laclau’s theory with other methodological perspectives are discussed, and a new research model is suggested, which is later applied in the discourse analysis of the political party “The Way of Courage.”